2010
DOI: 10.1038/ismej.2010.49
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity and community structure of anaerobic gut fungi (phylum Neocallimastigomycota) in ruminant and non-ruminant herbivores

Abstract: The phylogenetic diversity and community structure of members of the gut anaerobic fungi (AF) (phylum Neocallimastigomycota) were investigated in 30 different herbivore species that belong to 10 different mammalian and reptilian families using the internal transcribed spacer region-1 (ITS-1) ribosomal RNA (rRNA) region as a phylogenetic marker. A total of 267 287 sequences representing all known anaerobic fungal genera were obtained in this study. Sequences affiliated with the genus Piromyces were the most abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
230
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(250 citation statements)
references
References 43 publications
14
230
2
4
Order By: Relevance
“…Thus, our study confirms that lakes are undersampled for zoosporic fungal diversity and that these ecosystems harbor a highly unexplored zoosporic fungal diversity mainly within the order Chytridiales and Rhizophydiales, known to contain both saprobes and algal parasites (Letcher et al 2008a, Vélez et al 2011. Interestingly, 2 environmental sequences (LLMB10I and LLMBE 10II) affiliated to Neocallimastigomycota, which are known to be essentially anaerobic (Liggenstoffer et al 2010), were detected. Only 1 previous similar study conducted by Slapeta et al (2005) in a shallow freshwater pond also detected 1 environmental sequence related to this phylum.…”
Section: Zoosporic Fungal Diversity and Phylogenysupporting
confidence: 62%
“…Thus, our study confirms that lakes are undersampled for zoosporic fungal diversity and that these ecosystems harbor a highly unexplored zoosporic fungal diversity mainly within the order Chytridiales and Rhizophydiales, known to contain both saprobes and algal parasites (Letcher et al 2008a, Vélez et al 2011. Interestingly, 2 environmental sequences (LLMB10I and LLMBE 10II) affiliated to Neocallimastigomycota, which are known to be essentially anaerobic (Liggenstoffer et al 2010), were detected. Only 1 previous similar study conducted by Slapeta et al (2005) in a shallow freshwater pond also detected 1 environmental sequence related to this phylum.…”
Section: Zoosporic Fungal Diversity and Phylogenysupporting
confidence: 62%
“…␤-Glucosidases are classified by CAZy into two families: GH1 and GH3 (69,146,147). The structure of a GH1 ␤-glucosidase from T. reesei (TrBgl2; PDB entry 3AHY) has a classical (␣/␤) 8 -TIM barrel fold. The active site of TrBgl2 consists of a 15-to 20-Å-deep slot-like cleft located on connecting loops at the C-terminal end of the ␤-sheets of the TIM barrel (148).…”
Section: -5-␦-lactones (134)mentioning
confidence: 99%
“…Fungi are also present in soil and in the rumina of herbivores and are rich in polysaccharide-degrading enzymes and active in recycling plant cell walls (8,9). For example, Aspergillus nidulans grown on sorghum stover under solid-state culture conditions secreted a total of 294 proteins, predominantly hemicellulases, cellulases, polygalacturonases, chitinases, esterases, and lipases, over a 2-week period, while the fungus used only 30% of the total available hemicellulose and cellulose accessible from sorghum stover (10).…”
mentioning
confidence: 99%
“…It was surprising that such a large dataset should yield no sequences falling into the Buwchfawromyces clade. However, examination of the primers used by Liggenstoffer et al (2010) revealed the presence of mismatches between the forward primer (MN100modi-fied; 5'-TCCTACCCTTTGTGAATTTG-3') and the cognate sequences found in members of the Buwchfawromyces clade (TCCTACCCTTTGTGAATTGT or TC-CTTACCCTTTGTGAACTGA) (Suppl. material 2).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…As the amount of DNA barcode data (mostly based on the internal transcribed spacer regions, ITS1 and ITS2), both for pure cultures and from environmental DNA sequencing projects has increased, it has become apparent that the six existing clades represent only a subset of the full diversity of the anaerobic fungi (Griffith et al 2010). For instance, Liggenstoffer et al (2010) generated 250,000 ITS1 sequences from a diverse range of host species and identified eight potentially novel clades. Furthermore, reconciliation of morphological features and DNA barcode data has led to the reassignment of some taxa (Fliegerová et al 2012).…”
Section: Introductionmentioning
confidence: 99%